AN ANALYSIS OF DEIXIS IN BLACK SWAN MOVIE SCRIPT - Kurnia Saputri (Global Expert: Jurnal Bahasa dan Sastra, 2016)
This study was entitled “An Analysis of Deixis in Black Swan Movie Script”. The problems of this study were what types of deixis are used in Black Swan Movie Script? and what is the dominant deixis used in Black Swan Movie Script? The objectives of this study were to find the types of deixis and to find the dominant of deixis in Black Swan Movie Script. This study only focused on movie script. This study was purposed to find out the types and the dominant of deixis are used in Black Swan Movie Script. This script got from internet. The study applied descriptive qualitative method. The following steps, it applied was the first, this study looked for the movie, the second, this study watched the movie, then, looked for the movie script of the movie “Black Swan”, the fourth, this study identified the sentence of the movie script based on four types of deixis. From the analysis, it is found that there are four types; personal deixis, spatial deixis, temporal deixis, and discourse deixis and the most dominant deixis used in Black Swan Movie Script is personal deixisKeyword : deixis, Black Swan, and Movie Script